Low- and intermediate-energy stopping power of protons and antiprotons in solid targets - Montanari, Claudia Carmen (2017)
In this paper we propose a nonperturbative approximation to electronic stopping power based on the central screened potential of a projectile moving in a free-electron gas, by Nagy and Apagyi [Phys. Rev. A 58, R1653 (1998)PLRAAN1050-294710.1103/PhysRevA.58.R1653]. We used this model to evaluate the energy loss of protons and antiprotons in ten solid targets: Cr, C, Ni, Be, Ti, Si, Al, Ge, Pb, Li, and Rb. They were chosen as canonicals because they have reliable Wigner-Seitz radius, rs=1.48 to 5.31, which cover most of the possible metallic solids. Present low-velocity results agree well with the experimental data for both proton and antiproton impact. Our formalism describes the binary collision of the projectile and one electron of the free-electron gas. It does not include the collective or plasmon excitations, which are important in the intermediate- and high-velocity regime. The distinguishing feature of this contribution is that by using the present model for low to intermediate energies and the Lindhard dielectric formalism for intermediate to high energies, we describe the stopping due to free-electron gas in an extensive energy range. Moreover, by adding the inner-shell contribution using the shellwise local plasma approximation, we are able to describe all the available experimental data in the low-, intermediate-, and high-energy regions.